Investigating the Factors Affecting Virtual Team Performance in Public Organizations - El Yousfi, Fatima; Anand, Amitabh (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Despite numerous studies in private organizations on Virtual Teams (VTs), very little has been documented about the factors affecting the performance of VT members in public organizations. To fill this gap, this paper takes a qualitative and exploratory stance to explore this topic in Canadian public organizations. Through extensive interviews with 34 managers and employees, the findings uncovered three key issues that affect VT performance: virtual leadership characteristics, team member characteristics, and task characteristics, highlighting the implications of these issues and how they could be addressed. Finally, the findings offer managerial implications to support managers involved in VT management.